Application of the Implicit Relational Assessment Procedure (IRAP) to Evaluate Bias Related to Intimate Partner Violence (IPV) within Child Welfare - Sereno, Michelle (International Journal of Criminology and Sociology, 2024)
Problematic bias evidenced by child welfare professionals in relation to Intimate Partner Violence (IPV) victimization can negatively impact outcomes for children and families in the foster care system. The literature supports malleability of IPV-related bias in response to training interventions. These studies rely heavily on self-report measures. Self-report tools capture extended responses (explicit bias). These measures are less likely to reflect immediate responses (implicit bias). Combining explicit and implicit measures may inform a more comprehensive understanding. Purpose of Study: We employed a multi-method protocol to measure bias evidenced by dependency professionals in relation to IPV victimization. Method: Participants completed the Implicit Relational Assessment Procedure - Intimate Partner Violence (IRAP-IPV), an explicit analog of the IRAP-IV, and a gender-neutral version of the Domestic Violence Myth Acceptance Scale (GN-DVMAS). Principle Results: Results show expected divergence between explicit and implicit measures, with stronger positive valuation reflected on the explicit tools. We compared IRAP-IPV scores across in person and virtual groups. While statistical analyses indicate no significant between-group differences, divergence is evident upon visual inspection. Conclusion: This study supports the importance of multi-method measurement when evaluating IPV-related bias. We discuss results in terms of social and contextual factors within child welfare that may influence how dependency professionals respond to IPV. We offer recommendations for promoting a more equitable child welfare experience for victim-survivors, their families, and the professionals who serve them.